Recurrence of sarcoid granulomas in lung transplant recipients is common and does not affect overall survival - Schultz, Hans Henrik Lawaetz; Andersen, C. B.; Steinbrüchel D.; Perch, M.; Carlsen, J.; Iversen, M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Background: Sarcoidosis represents 2,5% of all indications for lung transplantation and criteria are generally assumed to be the same as for pulmonary fibrosis. Recurrence of granulomas in transplanted lungs has earlier been proved to derive from recipient immune cells, but its role in relation to lung function and overall survival after lung transplantation remains uncertain. Objective: To identify recurrent granuloma in transbronchial biopsies in patients receiving lung transplant because of sarcoidosis, and relate the findings to overall survival and lung function. Design: A total of 620 patients were transplanted at this centre from 1992 until august 2012. This study comprised all patients (n=25) transplanted due to pulmonary sarcoidosis. Lung functions, trans-bronchial biopsies, and survival were compared in patients with and without recurrence of granulomas. Granulomas were defined as non-necrotizing epitheloid granulomas with multinucleated giant cells according to standard criteria (formation of epitheloid giant cells) without presence of infection. Conclusions: Approximately 30% of lung transplant recipients due to sarcoidosis have recurrence of sarcoid granulomas. Recurrence of granulomas does not affect overall survival or lung function.